Analysis Of Information System Implementation Electronic Medical Record With Technology Acceptance Model - Edy Susanto; Iswari Septiana Nindi Wulandari; Nadilla Putri Melisa; Restu Indriani; Rosari Cahyaning Rastri; May Fatul Uul Qoriah; Novita Sri Wulandari (Jurnal Rumpun Ilmu Kesehatan, 2021)
At the Health Center an electronic medical record information system (RME) is used in the department registration, poly general, poly elderly, poly tooth, poly MCH, room integrated, room mtbs, psychology, physiotherapy, laboratory and nutrition. Perceived use describes the extent to which they can accept A technology specifically system record medical electronic (RME). Objective study This For analyze how much the perception and use of the electronic medical record information system (RME), how simple and easy it is to implement an electronic medical record information system (RME). And how much big enhancement performance can achieved blessing exists system information That, so analysis with the Technology Acceptance Model method was used . The type of research that used is descriptive analytic. Collection And study with use, observation And questionnaire. The subject population in this study were 30 officers who use information systems RME. The object of this study is the implementation of the Electronic Medical Record Information System. Results between independent variables and dependent variables on system users RME information did not have a significant effect, namely 0.813 No according to decision. Simple linear regression test where Ho is greater than 0.05 then the hypothesis beginning rejected that No There is influence between variable free to variable bound in user RME information system.